The Power of One on One Human Libraries and the challenges of antiracism work - Dreher, Tanja (UTS Shopfront Series, 2012)
This book provides an overview of the innovative social inclusion initiatives known as human or living libraries. It is the first comprehensive and independent analysis of Human Libraries in Australia. The book provides an overview of Human Library practices and identifies key challenges for policymakers and practitioners while contributing to scholarly debates on anti-racism work and on the benefits and limits of cross-cultural contact or dialogue within that work.